Studies on the Phytodiversity of a Sacred Grove and its Traditional Uses in Karaikal District, U.T. Puducherry - Sambandan, K; Dhatchanamoorthy, N (Journal of Phytology, 2012)
India is a land of diverse natural resources with the strong traditions of nature conservation practices. The sacred groves are the representatives of climax vegetation and exhibit the diversity of species such as trees, climbers, epiphytes and other shade loving herbs. Well-preserved sacred groves are storehouses of valuable medicinal and other plants having high economic value and serve as a refuge to threatened species. The present paper deals with floristic composition of angiosperms grown in a sacred grove located in Karaikal district and to document its traditional medicinal uses. The present work also elucidates the species composition of 59 plants species of flowering plants which spreads in 55 genera and 30 families. Many rural people in the district were using the plants from the sacred grove to cure many common diseases. This kind of degraded sacred groves should be immediately restored or regenerated using appropriate technologies and by raising awareness among the rural people regarding the importance of sacred grove and its conservation.